ZERO EMISSIONS CONCEPT - Zavargo, Z.; Jokić, A. (Journal of Engineering & Processing Management, 2010)
While proposed concepts to minimize, reuse and recycle wastes have generally, not solved the negative effects on environment, zero emissions concepts have arisen. The term Zero Emissions attracted special attention, as it is easily comprehensible and does not require translations. This concept is drawing mounting interest all around the world. In the recent years since the amount of waste generated is increasing, the demand of energy is pressed, and availability of natural resources is limited, the use of waste has become one of the main field of interest for researchers. This concept foreseen input streams to an industrial complex being used in the final products or converted into value added inputs for other industries or processes. It implies the optimization throughout an integrated system of processes and requires the industries to redesign manufacturing processes to resourcefully use both raw material within the process and waste towards the aim of sustainability. That implies exploitation of waste that can be brought to at sustainable levels in closed circle processes, ideally, the integrated process produces no wastes. Waste can be a resource if it is put in the right place.